LAYANAN KONSELING TRAUMATIK BAGI KORBAN BENCANA BANJIR DI KONAWE UTARA - Sumarlin, Sumarlin; Hamdiansah, Hamdiansah; Silondae, Dodi Priyatmo; Yusuf, Harlin (WELL-BEING: Journal of Social Welfare, 2020)
Traumatic counseling is a counselor's effort to help traumatized clients through the process of personal relationships so that clients can understand themselves in relation to the trauma they have experienced and try to overcome them as best they can. As a natural process, flooding occurs due to the very high flow of river water that exceeds the capacity of the river channel and then overflows into the surrounding area. Meanwhile, flooding can also occur due to human error. There are two possible assistance counseling services that can be applied to overcome post-trauma, namely: 1) psychological reconstruction through help to overcome the past, and 2) social reconstruction through restoring relationships. In its implementation, a communication facility team needs to be formed to provide services and activities regarding conflict for each victim. Therefore, the government should immediately dispatch volunteers who are tasked with providing traumatic counseling services in the form of trauma counseling services which is no less important for flood victims to prioritize.